Description of the male of Lasiotheus Paclt, 1963, its implication in Atelurinae supra-generic taxonomy and keys for the genera (Insecta: Zygentoma) - Mendes, Luis F. (Zootaxa, 2012)
The male is described by the first time for Lasiotheus Paclt, 1963 (Nicoletiidae: Atelurinae) upon a sample of L. nanus (Escherich, 1903) obtained in Gabon, from where the genus was previously unknown. The real independence of Lasiotheus relatively to Gastrotheus Casey, 1890 s.s. and to Pseudogastrotheus Mendes, 2003 (all previously considered under Gastrotheus Casey, 1890) is reinforced. Five tribes are recognized in Nicoletiidae (Atelurinae), characterized on morphological characteristics shared by groups of genera: Atelurini Remington, 1954, Atopatelurini n. tribe, Dinatelurini n. tribe, Dionychellini n. tribe and Grassiellini n. tribe. Identification keys are proposed to the ca. 70 genera today known in the subfamily.